1996
DOI: 10.1016/s1074-7613(00)80681-0
|View full text |Cite
|
Sign up to set email alerts
|

Mice Lacking the MHC Class II Transactivator (CIITA) Show Tissue-Specific Impairment of MHC Class II Expression

Abstract: CIITA activates the expression of multiple genes involved in antigen presentation and it is believed to be required for both constitutive and IFN gamma-inducible expression of these genes. To understand the role of CIITA in vivo, we have used gene targeting to generate mice that lack CIITA. CIITA-deficient (-/-) mice do not express conventional MHC class II molecules on the surface of splenic B cells and dendritic cells. In addition, macrophages resident in the peritoneal cavity do not express MHC class II mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
284
2
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 334 publications
(304 citation statements)
references
References 47 publications
17
284
2
1
Order By: Relevance
“…Particularly convincing support was provided by the fact that MHC-II expression is abolished in CIITA-deficient BLS patients and CIITA knockout mice [2,3,19,25,26]. In both cases, no pathological phenotypes distinct from those arising from the absence of MHC-II-mediated Ag presentation have been documented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly convincing support was provided by the fact that MHC-II expression is abolished in CIITA-deficient BLS patients and CIITA knockout mice [2,3,19,25,26]. In both cases, no pathological phenotypes distinct from those arising from the absence of MHC-II-mediated Ag presentation have been documented.…”
Section: Discussionmentioning
confidence: 99%
“…Tg mice and littermate controls were sexmatched, over 8 wk old and housed under conventional conditions. CIITA and H2-Aa knockout mice backcrossed onto a C57B6/J background were provided by C. H. Chang and H. Bluethmann [25,29]. CIITA-p(III+IV) mice were on a mixed Sv129 Â C57BL/6 background [19].…”
Section: Micementioning
confidence: 99%
“…Initial studies found that NLR family member CIITA could regulate the MHC class I gene activation through overexpression system in vitro (Martin et al, 1997;Williams et al, 2003). However, the expression of MHC class I genes was not affected in Ciita-defi cient mice (Chang et al, 1996), suggesting that there may be unidentifi ed regulators for MHC class I genes. As mentioned of NLRC5 was impaired in Stat1 -/-T cells after TCR activation which can promote IFN-γ production.…”
Section: Structure Of Nlrc5mentioning
confidence: 99%
“…Over a decade ago, it was reported that the class II transactivator (CIITA also known as NLRA), was essential for conventional MHC class II gene expression and consequently CD4 + T cell development and activation through genetic study of Ciita-deficient mice (Chang et al, 1996). Therefore, CIITA represents a master regulator of MHC class II gene expression (Williams et al, 1998;LeibundGut-Landmann et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…MHC class II genes are constitutively expressed in B cells and dendritic cells (DC) and can be induced in macrophages by IFN-γ (Steinman et al, 1999;Reith et al, 2005). Both constitutive and inducible MHC class II gene expression requires the class II transactivator (CIITA) (Reith et al, 2005;Steimle et al, 1993;Chang et al, 1996;LeibundGutLandmann et al, 2004). CIITA is not a DNA binding protein.…”
Section: Introductionmentioning
confidence: 99%